Management of Primary Squamous Cell Carcinoma of the Pancreas: A Case Report - Guo, Danling; Chen, Chao; Lv, Sangying; Wu, Guanzuan; Shi, Wei; Li, Huaifeng; Hu, Hongjie (Frontiers in Surgery, 2021)
Introduction: Primary squamous cell carcinoma of the pancreas (SCCP) is a rare malignant tumor that has been reported in individual case reports only. The clinical data on primary SCCP treatment are limited. Therefore, the appropriate management strategy for this disease should be standardized. Case Presentation: We present the case of a 63-year-old man admitted to our hospital for upper left abdominal pain for two months without weight loss or jaundice. Enhanced computed tomography(CT) and magnetic resonance imaging(MRI) of the abdomen revealed a mixed solid and cystic lesion in the pancreatic tail, measuring 35 × 37 mm in maximum diameter with enhancement. The patient was diagnosed with primary SCCP without metastasis, based on radiological and pathological findings. He did not receive neoadjuvant therapy postoperatively and was followed up by CT and MRI for 18 months without recurrence or metastasis. Result: Complete resection is the most effective treatment for early stage primary SCCP. Abdominal MRI is an effective imaging tool for preoperative evaluation and postoperative follow-up of primary SCCP. The need for neoadjuvant therapy depends on various factors. Conclusion: Primary SCCP is a tumor with poor prognosis. Pancreatic cancer risk factor control, early accurate radiologic evaluation, and individualized treatment strategies improve the quality of life and prolong the overall survival period of patients.